Unfired hollow artificial aggregate and preparation method thereof

By using the design of the hydrogel core and alkali excitation material binder layer in artificial aggregate, combined with the mixed granulation process of regenerated micropowder and granulated blast furnace slag, the high energy consumption and cylinder of artificial aggregate in the prior art are solved. Due to the problem of low compressive strength, burn-free hollow artificial aggregate with low bulk density and high compressive strength is prepared, which is suitable for thermal insulation and insulation applications of building structures.

CN119390382AActive Publication Date: 2025-02-07XI'AN UNIVERSITY OF ARCHITECTURE AND TECHNOLOGY

Patent Information

Application Number
CN202411532573.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

In the prior art, artificial aggregates have high sintering temperature, large energy consumption, high stacking density and low cylinder pressure strength, making it difficult to meet the needs of building structures.

Method used

Hydrogel is used as the core material and alkali excitation material is used as the intermediate binder layer. Regenerated micro powder and granulated blast furnace slag powder are mixed to prepare hollow-free artificial aggregate.

Benefits of technology

It achieves low bulk density and high single-particle compressive strength, energy saving and emission reduction, and is suitable for thermal insulation walls and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390382A_ABST
    Figure CN119390382A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: mixing agar, carrageenan and a gelatin solution to prepare a core material hydrogel; mixing sodium hydroxide, water glass and water to prepare an intermediate binder A; mixing the regenerated micro powder with biochar to prepare an intermediate binder B; mixing the binder A and the binder B to obtain an intermediate binder; mixing the regenerated micro powder and the granulated blast furnace slag powder to obtain an outer core material; putting hydrogel into the binder A and the binder B, wrapping the surface of the hydrogel with a mixed binder solution, putting the hydrogel into the binder B, obtaining a material C, and drying and curing the material C to obtain a hollow core; and granulating the hollow core, spraying the binder A while pouring the shell powder to form a spherical aggregate, and rolling the spherical aggregate at a rotating speed to obtain the unfired hollow artificial aggregate. According to the preparation method disclosed by the invention, the unfired hollow artificial aggregate with relatively low bulk density and relatively high single-particle compressive strength is prepared by taking the regenerated micro powder and the slag solid waste material as a shell and the hydrogel as an inner core in an alkali excitation manner.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid waste resource utilization and building materials, and relates to a fire-free hollow artificial aggregate and a preparation method thereof. Background Art

[0002] With the continuous exploitation and utilization of natural sand and gravel resources, the shortage of natural sand and gravel resources in my country is becoming more and more serious. Using artificial aggregates to replace natural aggregates is an important way to solve the shortage of natural sand and gravel. There are two types of curing processes for artificial aggregates. One is the sintering hardening process, which consumes a lot of energy and has the risk of secondary pollution; the other is the cold hardening process, which uses solid waste such as construction waste (recycled micropowder) and slag, and can be prepared by curing at room temperature, saving energy and reducing emissions.

[0003] Recycled micro powder is a fine powder with a particle size less than 0.15mm produced in the process of recycling recycled concrete aggregate. The particle surface is rough and porous, with high water absorption and low activity, resulting in low utilization rate of recycled micro powder.

[0004] CN118145905A (application publication date June 7, 2024) The patent applies for a coal-based solid waste lightweight high-strength aggregate and its preparation method and application, which is mainly made of coal gangue and coal gasification ash of a certain particle size mixed evenly, granulated and sintered to form a bulk density of 900kg / m 3 ~1100kg / m 3 The granular product has a single particle compressive strength of 8-20MPa. The product is calcined at a high temperature of 1000-1200℃ and has a high energy consumption.

[0005] Patent CN117510225A (application publication date February 6, 2024) applied for a method for preparing gypsum-based lightweight hollow aggregates, which mainly uses molten paraffin, adds mixed reactants, granulates before the paraffin is completely hardened to obtain aggregates, and then places them in a microwave oven for irradiation to obtain gypsum-based lightweight hollow aggregates. Among them, the preparation process of gypsum-based cementitious materials adopts a sintering process, which has high energy consumption and low cylinder pressure strength (1.8~3.1MPa).

[0006] Patent CN115259815A (application publication date November 1, 2021) applied for a method for preparing artificial aggregates from metal tailings, which mainly includes: mixing metal tailings, gypsum and auxiliary agents, granulating them through a high-speed granulator, and the bulk density is 1282-1320 kg / m 3 The cylinder compressive strength of copper tailings ceramsite is 7-15MPa. The aggregate of the invention has high cylinder compressive strength and high bulk density.

[0007] The above-mentioned solid artificial aggregates in the prior art are limited to use in load-bearing structural components of building structures, and have the problems of high aggregate sintering temperature and high energy consumption; high stacking density, and low cylinder pressure strength even though a non-sintering process is used. It is urgent to provide a method for preparing a non-fired hollow artificial aggregate. Summary of the invention

[0008] In order to solve the above-mentioned defects existing in the prior art, the purpose of the present invention is to provide a fire-free hollow artificial aggregate and a preparation method thereof. The present invention uses the prepared hydrogel as a bonding layer template. When the bonding layer is dried, the moisture in the hydrogel is discharged to form a hollow structure; by introducing an alkali-activated material into the middle adhesive layer as a template for the fire-free hollow artificial aggregate, recycled micropowder and granulated blast furnace slag powder are mixed and granulated, and the prepared fire-free hollow artificial aggregate has a lower bulk density and a higher single particle compressive strength.

[0009] The present invention is achieved through the following technical solutions.

[0010] One aspect of the present invention provides a method for preparing a fire-free hollow artificial aggregate, comprising the following steps: A. Preparation of core materials: a1) Mix gelatin and water in a mass ratio of (1-2):(4-7) to prepare a gelatin solution; a2) pouring agar and carrageenan into hot water according to the mass ratio of agar, carrageenan and water (1-2): (0.1-0.5): (5-10), mixing them evenly, mixing the mixture with gelatin solution at a mass ratio of 1:1, and dropping the mixture into a spherical mold to prepare a spherical hydrogel; B. Preparation of intermediate binder: b1) Sodium hydroxide, water glass and water are mixed in a mass ratio of (1-2):(5-10):(1-5) to obtain an intermediate binder A; b2) mixing the regenerated micro powder and the biochar in a mass ratio of (1-2): (0.01-0.02) to prepare an intermediate binder B; b3) mixing and stirring the binder A and the binder B in a mass ratio of binder A:B=1:1.2 to obtain an intermediate binder; C. Shell material preparation: The recycled micro powder and the granulated blast furnace slag powder are mixed in a mass ratio of (5-10):(1-5) to obtain a shell powder; D. Preparation of unburned hollow artificial aggregate: d1) placing the core material hydrogel into a mixed solution of binders A and B, coating the surface of the hydrogel with the binder and placing it into binder B to obtain material C, drying and curing material C to obtain a hollow core; d2) Pour a small amount of shell powder into the granulator, place the solidified hollow core in the granulator, spray binder A while pouring the shell powder to form uniform spherical aggregates, and roll the spherical aggregates at a certain speed to obtain unburned hollow artificial aggregates of a certain particle size; The granulated artificial aggregate is cured in a temperature and relative humidity environment.

[0011] Preferably, in step a1), gelatin and water are mixed and the gelatin powder absorbs water and swells for 1 to 2 hours.

[0012] Preferably, in step a2), agar and carrageenan are poured into hot water at 70-90° C. and stirred thoroughly; the mixture is placed in a refrigerator and refrigerated for 2-3 hours to prepare a hydrogel.

[0013] Preferably, in step C, the regenerated micro powder and granulated blast furnace slag powder are placed in a granulator, stirred for 2 to 5 minutes, and rolled at a rotation speed of 10 to 20 r / min.

[0014] Preferably, in step d1), material C is placed in a drying oven at a temperature of 25-35° C. for curing for 18-36 hours.

[0015] Preferably, in step d2), the pelletizing is completed at a rotation speed of 10-20 r / min for 20-30 min, and when the aggregates agglomerate to 10-15 mm.

[0016] Preferably, in step d2), the granulated artificial aggregate is cured for 28 days in an environment with a temperature of 20±2° C. and a relative humidity of 95% RH or higher.

[0017] Preferably, the oxide content of the regenerated micropowder material is SiO2≥48.85%; CaO≥22.11%; Al2O3≥13.28%; Fe2O3≥6.44%; MgO≥2.7%; and SO3≥0.67%.

[0018] Preferably, the oxide content of the granulated blast furnace slag material is SiO2≥34.2%; CaO≥34%; Al2O3≥17.6%; Fe2O3≥1.01%; MgO≥6.21%; and SO3≥5.36%.

[0019] Another aspect of the present invention provides a fire-free hollow artificial aggregate prepared by the method for preparing the fire-free hollow artificial aggregate.

[0020] The present invention adopts the above technical solution, which has the following beneficial effects: 1. The hydrogel prepared by mixing agar, carrageenan and gelatin solution in the present invention can discharge water through the pore structure of the biochar in the binder layer after the middle binder layer is dried to form a hollow structure.

[0021] 2. The intermediate binder of the present invention uses regenerated micropowder and biochar as precursors and a mixture of sodium hydroxide, water glass and water as an activator to form an alkali activation system, which can form a gel with a certain strength in a relatively short time.

[0022] 3. The present invention adopts recycled micro powder and granulated blast furnace slag powder to mix and granulate to obtain a fire-free hollow artificial aggregate; it has a lower bulk density and a higher single particle compressive strength.

[0023] 4. The present invention utilizes solid wastes such as construction waste (recycled micropowder) and slag, solves the problem of accumulation and land occupation, and achieves energy conservation and emission reduction.

[0024] 5. The present invention adopts cold hardening process, uses solid waste materials such as recycled micropowder and slag as the shell, uses hydrogel as the core, and uses alkali excitation to prepare a bulk density of 923kg / m 3 The unfired hollow artificial aggregate has a single particle compressive strength of about 4.5 MPa and has good application prospects in thermal insulation walls. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] The drawings described herein are used to provide a further understanding of the present invention, constitute a part of the present application, and do not constitute an improper limitation of the present invention. In the drawings: Figure 1 Schematic diagram of the shape of aggregate of the present invention. DETAILED DESCRIPTION

[0026] The present invention will be described in detail below in conjunction with the accompanying drawings and specific embodiments. The exemplary embodiments and descriptions of the present invention are used to explain the present invention but are not intended to limit the present invention.

[0027] The hollow artificial aggregate provided by the embodiment of the present invention comprises: an inner core material, an intermediate binder material and an outer core material, which are prepared by a cold hardening process.

[0028] The inner core materials include gelatin, carrageenan and agar; the middle binder materials include sodium hydroxide, water glass, recycled micropowder and biochar; and the outer core materials include granulated blast furnace slag and recycled micropowder.

[0029] The method for preparing hollow artificial aggregate of the present invention specifically comprises the following steps: A. Preparation of core materials: a1) Prepare gelatin solution: Mix gelatin and water in a gelatin to water mass ratio of (1-2):(4-7). Allow the gelatin powder to absorb water and swell for 1-2 hours. Stir the gelatin solution until evenly mixed and set aside.

[0030] a2) Preparation of hydrogel: Pour agar and carrageenan into hot water at 70-90°C in a mass ratio of (1-2): (0.1-0.5): (5-10) of agar, carrageenan and water. After thorough stirring, mix with gelatin solution in a mass ratio of 1:1. Drop the mixture into a silicone mold using a rubber-tipped dropper and refrigerate in a refrigerator for 2-3 hours to prepare a spherical hydrogel.

[0031] B. Preparation of intermediate binder: b1) Preparation of Binder A: Sodium hydroxide, water glass and water are mixed in a mass ratio of (1-2): (5-10): (1-5) to obtain an intermediate binder A; b2) Preparation of Binder B: The regenerated micro powder and the biochar are mixed in a mass ratio of (1-2): (0.01-0.02) to obtain an intermediate binder B; b3) Preparation of intermediate binder: Mix binder A and binder B in a mass ratio of binder A:B=1:1.2 and stir evenly for use.

[0032] C. Shell material preparation: Place the recycled micro powder and granulated blast furnace slag powder in a granulator according to the mass ratio of (5-10): (1-5), stir for 2-5 minutes to fully mix the powders, and set aside.

[0033] D. Preparation of unburned hollow artificial aggregate: d1) Preparation of hollow core: The core material hydrogel is placed in a mixed solution of binders A and B, and the surface of the hydrogel is coated with the mixed binder solution and then placed in binder B, so that the surface of the hydrogel is coated with the powder to obtain material C, and material C is placed in a drying oven at a temperature of 25-35°C for 18-36 hours to obtain a hollow core; d2) Mixing and granulation: The prepared hollow core is used as raw material for granulation, and the prepared binder A is placed in a spray pot; first, a small amount of shell powder is poured into the granulator, and the solidified hollow core is placed in the disc granulator, while the binder A is sprayed, the shell powder is poured in to make it a uniform spherical aggregate, and it is rolled at a speed of 10~20r / min (to ensure that the aggregate is not thrown out of the disc granulator). The hollow core adheres to the surrounding outer core powder, making its own particle size larger. The granulation process lasts for 20~30 minutes. When the aggregate agglomerates to a particle size of 10~15mm, the granulation is completed, and the unburned hollow artificial aggregate is obtained. See the schematic diagram of the structure of the unburned hollow artificial aggregate. Figure 1 shown.

[0034] The granulated artificial aggregate is cured in an environment with a temperature of 20±2°C and a relative humidity of more than 95%RH for 28 days.

[0035] Disc granulator parameters: disc diameter 50cm, disc circle 12cm, inclination angle 30-60°. The invention introduces alkali-activated materials into the preparation of artificial aggregates to improve the performance of the aggregates. In order to reduce the weight of the aggregates, a hydrogel is used as the core, recycled micropowder and granulated blast furnace slag are used as the shell powders, and water glass and sodium hydroxide are used as activators to prepare the unfired hollow artificial light aggregates.

[0036] The hydrogel prepared by mixing agar, carrageenan and gelatin solution is in a gel state at 0-5°C and in a liquid state at 25-35°C. The gelled hydrogel is used as a spherical mold. The intermediate binder is attached to the surface of the hydrogel so that the binder forms an integral bonding layer. The bonding layer adopts an alkali-activated system and the bonding layer condenses quickly. The condensed structure is dried, the core material hydrogel decomposes and discharges water through the pore structure of the intermediate binder B biochar to form a bonding layer structure. The bonding layer is used as a mold to prepare the unburned hollow artificial aggregate. Then, the recycled micropowder and granulated blast furnace slag powder are mixed and granulated to obtain the unburned hollow artificial aggregate. It has a certain single particle compressive strength.

[0037] By introducing alkali-activated materials, high-quality unburned hollow artificial aggregates are made, which have high compressive strength and good density. Due to the hollow characteristics of the aggregate, it can be used in thermal insulation walls.

[0038] The hollow artificial aggregate material requirements of the present invention are as follows: (1) Recycled micropowder: The recycled micropowder used in this experiment comes from the waste concrete aggregate of Shaanxi Hongwei Ecological Environmental Protection Co., Ltd. The company produces a large number of building solid particles with a particle size of less than 4.75 mm in the process of crushing construction waste. The solid particles are dried at 80 0 C, 24h, then ball milled for 40min using a planetary ball mill (model XU-XQM-4A) at a speed of 300r / min, and sieved through a 0.15mm standard square hole sieve to obtain the test raw material construction waste powder with a particle size of less than 150μm. The oxide content of the material is detailed in Table 1.

[0039] (2) Granulated blast furnace slag: S95 slag produced by Henan Wuhu Environmental Protection Technology Co., Ltd., with a specific surface area of ​​430m 2 / kg, about 500 mesh, the oxide content of the material is shown in Table 1.

[0040] (3) Sodium hydroxide: Shanghai test, white uniform flaky solid, purity 98±1%.

[0041] (4) Water glass: It is composed of 65.8% water and 30.6% industrial grade sodium silicate powder with a purity of 98%. Correspondingly, it contains 8.2% Na2O, 26% SiO2 and 65.8% H2O (by weight), and the modulus (molar ratio of SiO2 to Na2O) of water glass powder is 3.2.

[0042] (6) Other materials: Gelatin powder; the main component is animal collagen, with a gel strength of 250 and a mesh size of about 80. Carrageenan: extracted from agar, 100 mesh. Agar: extracted from seaweed, 100 mesh.

[0043] Table 1 Material oxide content

[0044] The S95 slag contains a large amount of active SiO2 and Al2O3. Under the action of strong alkali, the slag undergoes crystal reconstruction to form a cementitious material with oxygen-silicon tetrahedron and aluminum-oxygen tetrahedron as the main components, presenting a three-dimensional network structure in space. The recycled micropowder contains more SiO2 and Al2O3. The recycled micropowder after ball milling not only has a certain volcanic ash activity, but also provides nucleation sites for hydration products, playing a filling role.

[0045] The present invention is further illustrated by examples below: Example 1 A. Preparation of core materials: a1) Prepare gelatin solution: Mix gelatin and water in a mass ratio of 1:5.8. Allow the gelatin powder to absorb water and swell for 1 hour. Stir the gelatin solution evenly for later use.

[0046] a2) Preparation of hydrogel: Pour agar and carrageenan into 80°C hot water at a mass ratio of 1:0.25:7.7, stir thoroughly, and then mix with gelatin solution at a mass ratio of 1:1. Use a rubber-tipped dropper to drop the mixture into a silicone mold and refrigerate in a refrigerator for 2 hours to prepare a spherical hydrogel.

[0047] B. Preparation of intermediate binder: b1) Preparation of Binder A: Sodium hydroxide, water glass and water are mixed in a mass ratio of 1:8:2.4 to obtain an intermediate binder A; b2) Preparation of Binder B: The regenerated micro powder and biochar are mixed in a mass ratio of 1:0.01 to obtain an intermediate binder B; b3) Preparation of intermediate binder: Mix binder A and binder B in a mass ratio of binder A:B=1:1.2 and stir evenly for use.

[0048] C. Shell material preparation: Place the recycled micro powder and granulated blast furnace slag powder in a granulator at a mass ratio of 7:3, stir for 2 to 5 minutes to fully mix the powders, and set aside.

[0049] D. Preparation of unburned hollow artificial aggregate: d1) Preparation of hollow core: The core material hydrogel is placed in a mixed solution of binders A and B, and the surface of the hydrogel is coated with the mixed binder solution and then placed in binder B, so that the surface of the hydrogel is coated with the powder to obtain material C, and material C is placed in a drying oven at a temperature of 30°C for 24 hours to obtain a hollow core; d2) Mixing and granulation: The prepared hollow core is used as a raw material for granulation, and the prepared binder A is placed in a spray pot; first, a small amount of shell powder is poured into the granulator, and the solidified hollow core is placed in a disc granulator, and the shell powder is poured into the disc granulator while the binder A is sprayed to make it into a uniform spherical aggregate, which is rolled at a speed of 15 r / min (to ensure that the aggregate is not thrown out of the disc granulator). The granulation process lasts for 25 minutes. When the aggregate agglomerates to a particle size of 10 mm, the granulation is completed to obtain a fire-free hollow artificial aggregate.

[0050] The granulated artificial aggregate is cured in an environment with a temperature of 20±2°C and a relative humidity of more than 95%RH for 28 days.

[0051] Example 2 A. Preparation of core materials: a1) Prepare gelatin solution: Mix gelatin and water in a mass ratio of 1.5:4. Allow the gelatin powder to absorb water and swell for 2 hours. Stir the gelatin solution evenly for later use.

[0052] a2) Preparation of hydrogel: Pour agar and carrageenan into 70°C hot water at a mass ratio of 2:0.5:5, stir thoroughly, and then mix with gelatin solution at a mass ratio of 1:1. Use a rubber-tipped dropper to drop the mixture into a silicone mold and refrigerate in a refrigerator for 3 hours to prepare a spherical hydrogel.

[0053] B. Preparation of intermediate binder: b1) Preparation of Binder A: Sodium hydroxide, water glass and water are mixed in a mass ratio of 2:5:1 to obtain an intermediate binder A; b2) Preparation of Binder B: The regenerated micro powder and biochar are mixed in a mass ratio of 2:0.015 to obtain an intermediate binder B; b3) Preparation of intermediate binder: Mix binder A and binder B in a mass ratio of binder A:B=1:1.2 and stir evenly for use.

[0054] C. Shell material preparation: Place the recycled micro powder and granulated blast furnace slag powder in a granulator at a mass ratio of 5:1, stir for 2 minutes to fully mix the powders, and set aside.

[0055] D. Preparation of unburned hollow artificial aggregate: d1) Preparation of hollow core: The core material hydrogel is placed in a mixed solution of binders A and B, and the surface of the hydrogel is coated with the mixed binder solution and then placed in binder B, so that the surface of the hydrogel is coated with the powder to obtain material C, and material C is placed in a drying oven at a temperature of 35°C for 18 hours to obtain a hollow core; d2) Mixing and granulation: The prepared hollow core is used as a raw material for granulation, and the configured binder A is placed in a spray pot; first, a small amount of shell powder is poured into the granulator, and the solidified hollow core is placed in the granulator, and the shell powder is poured into the granulator while spraying the binder A to make it a uniform spherical aggregate. The prepared hollow core is used as a raw material for granulation, and the configured binder A is placed in a spray pot; first, a small amount of shell powder is poured into the granulator, and the solidified hollow core is placed in a disc granulator, and the shell powder is poured into the granulator while spraying the binder A to make it a uniform spherical aggregate. The aggregate is rolled at a speed of 10 r / min (to ensure that the aggregate is not thrown out of the disc granulator), and the granulation process lasts for 20 minutes. When the aggregate agglomerates to a particle size of 15 mm, the granulation is completed to obtain a fire-free hollow artificial aggregate.

[0056] The granulated artificial aggregate is cured in an environment with a temperature of 20±2°C and a relative humidity of more than 95%RH for 28 days.

[0057] Example 3 A. Preparation of core materials: a1) Prepare gelatin solution: Mix gelatin and water in a mass ratio of 2:7. Allow the gelatin powder to absorb water and swell for 1.5 hours. Stir the gelatin solution evenly for later use.

[0058] a2) Preparation of hydrogel: Pour agar and carrageenan into 90°C hot water at a mass ratio of 1.5:0.1:10, stir thoroughly, and then mix with gelatin solution at a mass ratio of 1:1. Use a rubber-tipped dropper to drop the mixture into a silicone mold and refrigerate in a refrigerator for 2.5 hours to prepare a spherical hydrogel.

[0059] B. Preparation of intermediate binder: b1) Preparation of Binder A: Sodium hydroxide, water glass and water are mixed in a mass ratio of 1.5:10:5 to obtain an intermediate binder A; b2) Preparation of Binder B: The regenerated micro powder and the biochar are mixed in a mass ratio of 1.5:0.02 to obtain an intermediate binder B; b3) Preparation of intermediate binder: Mix binder A and binder B in a mass ratio of binder A:B=1:1.2 and stir evenly for use.

[0060] C. Shell material preparation: The recycled micro powder and granulated blast furnace slag powder were placed in a granulator at a mass ratio of 10:5 and stirred for 5 minutes to fully mix the powders for standby use.

[0061] D. Preparation of unburned hollow artificial aggregate: d1) Preparation of hollow core: The core material hydrogel is placed in a mixed solution of binders A and B, and the surface of the hydrogel is coated with the mixed binder solution and then placed in binder B, so that the surface of the hydrogel is coated with the powder to obtain material C, and material C is placed in a drying oven at a temperature of 25°C for 36 hours to obtain a hollow core; d2) Mixing and granulation: The prepared hollow inner core is used as a raw material for granulation, and the prepared binder A is placed in a spray pot; first, a small amount of shell powder is poured into the granulator, and the solidified hollow inner core is placed in the granulator, and the shell powder is poured into the granulator while the binder A is sprayed to make it into a uniform spherical aggregate, which is rolled at a speed of 20 r / min (to ensure that the aggregate is not thrown out of the disc granulator). The granulation process lasts for 30 minutes. When the aggregate agglomerates to a particle size of 15 mm, the granulation is completed to obtain a fire-free hollow artificial aggregate.

[0062] The granulated artificial aggregate is cured in an environment with a temperature of 20±2°C and a relative humidity of more than 95%RH for 28 days.

[0063] Strength test: This experiment uses single particle strength (Crushing strength) to characterize the crushing strength of artificial aggregates, and sets normal granulated aggregates as the control group. The testing instrument is CMT-20 microcomputer-controlled electronic universal testing machine. Specific test method: Take 10 aggregates for each group of samples for testing. In order to eliminate the influence of aggregate size on strength results, the aggregate diameter is controlled at about 10mm. The diameter of the aggregate is the average value of the measured values ​​of a single aggregate in three directions. Place the aggregate between the loading plate and the support plate, and then apply pressure at a loading speed of 1mm / min until the aggregate is broken, and record the peak pressure when the aggregate is destroyed. The strength of the aggregate is calculated using the following calculation formula:

[0064] In the formula, σ c : compressive strength, unit: MPa; F c : Load at aggregate failure, unit N; d m : Average diameter of aggregate, in mm.

[0065] In the present invention, the hydrogel can be used as a mold of the middle bonding layer when in a gel state. After the water in the hydrogel evaporates, only a thin colloid shell is left, so that the artificial aggregate is in a hollow state, which can reduce the weight of the artificial aggregate.

[0066] The following is a comparison between a comparative example and the embodiments of the present invention to further illustrate the effects of the present invention.

[0067] Comparative Example 1 The lightweight hollow aggregate is prepared by using gypsum as the base, and the mass ratio of the materials used in the hollow aggregate is gypsum-based cementitious material: retarder: water reducer: thickener: short-cut fiber = 1: 0.1~0.3%: 0.1~0.5%: 0.05~0.3%: 1~2%. The raw materials are granulated before the paraffin wax is completely dried and hardened to obtain a mixed material ball; the gypsum mixture is coated on the surface of the mixed material ball, and the gypsum-based lightweight hollow aggregate is obtained after irradiation.

[0068] The performance test results of the embodiment and the comparative example are compared in Table 2.

[0069] Table 2 Performance of unburned hollow artificial aggregate (28 days)

[0070] It can be seen from Table 2 that the single particle strength of the unburned hollow artificial aggregate prepared by the cold hardening process of the present invention is not less than 4.38MPa, the cylinder pressure strength is not less than 4.54MPa, and the bulk density is not less than 946kg / m 3 The unfired hollow artificial aggregate material prepared by the present invention not only has high mechanical properties, but also has light weight, high strength, good stability, and is green and environmentally friendly. It is an unfired hollow artificial aggregate material with good processing performance.

[0071] The present invention is not limited to the above-mentioned embodiments. On the basis of the technical solution disclosed in the present invention, technicians in this field can make some substitutions and deformations to some technical features therein according to the disclosed technical content without creative labor, and these substitutions and deformations are all within the protection scope of the present invention.

Claims

1. A method for preparing a fire-free hollow artificial aggregate, characterized in that: The following steps are involved: A. Preparation of core materials: a1) mixing gelatin and water in a mass ratio of (1-2):(4-7) to prepare a gelatin solution; a2) pouring agar and carrageenan into hot water according to the mass ratio of agar, carrageenan and water (1-2): (0.1-0.5): (5-10), mixing them evenly, mixing the mixture with gelatin solution at a mass ratio of 1:1, and dropping the mixture into a spherical mold to prepare a spherical hydrogel; B. Preparation of intermediate binder: b1) mixing sodium hydroxide, water glass and water in a mass ratio of (1-2):(5-10):(1-5) to obtain an intermediate binder A; b2) mixing the regenerated micro powder and the biochar in a mass ratio of (1-2): (0.01-0.02) to prepare an intermediate binder B; b3) mixing and stirring the binder A and the binder B in a mass ratio of binder A:B=1:1.2 to obtain an intermediate binder; C. Shell material preparation: The recycled micro powder and the granulated blast furnace slag powder are mixed in a mass ratio of (5-10):(1-5) to obtain a shell powder; D. Preparation of unburned hollow artificial aggregate: d1) placing the core material hydrogel into a mixed solution of binders A and B, and placing the hydrogel surface after being coated with the mixed binder solution into binder B to obtain material C, and drying and curing material C to obtain a hollow core; d2) pouring a small amount of shell powder into a granulator, placing the solidified hollow core in the granulator, pouring the shell powder into the granulator while spraying the binder A to form a uniform spherical aggregate, and rolling the spherical aggregate at a certain speed to obtain a certain particle size of unburned hollow artificial aggregate; The granulated artificial aggregate is cured in a temperature and relative humidity environment.

2. The method for preparing the unburned hollow artificial aggregate according to claim 1, characterized in that: In step a1), gelatin is mixed with water and the gelatin powder absorbs water and swells for 1 to 2 hours.

3. The method for preparing the unburned hollow artificial aggregate according to claim 1, characterized in that: In step a2), agar and carrageenan are poured into hot water at 70-90° C. and stirred thoroughly; the mixture is placed in a refrigerator and refrigerated for 2-3 hours to prepare a hydrogel.

4. The method for preparing the unburned hollow artificial aggregate according to claim 1, characterized in that: In step C, the regenerated micro powder and granulated blast furnace slag powder are placed in a granulator and stirred for 2 to 5 minutes.

5. The method for preparing the unburned hollow artificial aggregate according to claim 1, characterized in that: In step d1), material C is placed in a drying oven at a temperature of 25 to 35° C. and cured for 18 to 36 hours.

6. The method for preparing the unburned hollow artificial aggregate according to claim 1, characterized in that: In step d2), the pelletizing is completed when the aggregate is aggregated to a particle size of 10 to 15 mm and the pelletizing is performed at a rotation speed of 10 to 20 r / min for 20 to 30 minutes.

7. The method for preparing the unburned hollow artificial aggregate according to claim 1, characterized in that: In step d2), the granulated artificial aggregate is cured for 28 days in an environment with a temperature of 20±2° C. and a relative humidity of 95% RH or more.

8. The method for preparing the unburned hollow artificial aggregate according to claim 1, characterized in that: The oxide content of the recycled micropowder material is SiO2≥48.85%; CaO≥22.11%; Al2O3≥13.28%; Fe2O3≥6.44%; MgO≥2.7%; SO3≥0.67%.

9. The method for preparing the unburned hollow artificial aggregate according to claim 1, characterized in that: The oxide content of granulated blast furnace slag material is SiO2≥34.2%; CaO≥34%; Al2O3≥17.6%; Fe2O3≥1.01%; MgO≥6.21%; SO3≥5.36%.

10. A fire-free hollow artificial aggregate prepared by the method for preparing fire-free hollow artificial aggregate according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of gypsum-based lightweight hollow aggregate

    CN117510225A

  • Coal-based solid waste lightweight high-strength aggregate as well as preparation method and application thereof

    CN118145905A

  • Micropore light-weight alumina refractory aggregate and preparation method thereof

    CN104177107A

  • Method for preparing PLGA-HA-PVA scaffold modified HA-PVA artificial cartilage materials

    CN106039418A

  • Preparation method of household garbage incineration bottom ash unfired porous artificial aggregate

    CN115466066A

Cited By

  • All-solid-waste-based core-shell type carbonized artificial aggregate and preparation method thereof

    CN120483600A

  • A full solid waste-based core-shell type carbonized artificial aggregate and a preparation method thereof

    CN120483600B

  • Cold-bonded artificial core-shell aggregate based on decoration waste regenerated sand powder and preparation method thereof

    CN121872694A